Peningkatan Pengetahuan Masyarakat untuk Pengelolaan Air Secara Berkelanjutan di Desa Pucangan Kabupaten Sukoharjo - Anna, Alif Noor; Sari, Dewi Novita; Cholil, Munawar; Priyana, Yuli; Fikriyah, Vidya Nahdhiyatul; Rudiyanto, Rudiyanto (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to increase community knowledge in sustainable water management in Pucangan Village, Kartasura District, Sukoharjo Regency. The service activities are carried out through workshops and Focus Group Discussion (FGD) methods targeting PKK mothers (family welfare development). Pre-tests and post-tests with questionnaires were carried out to measure the level of understanding of PKK mothers in managing water. The results of this community service show that there has been an increase in community knowledge about sustainable shallow groundwater management by an average of 8.8%, which consists of measuring water quality, management, and processing of groundwater.